2017
DOI: 10.11002/kjfp.2017.24.6.871
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of soymilk added with green tea and rosemary extract

Abstract: The objective of this study was to compare antioxidant activities of green tea, rosemary, lemon and bamboo leaves extracts using three different extraction methods (80% ethanol sonication extraction, distilled water autoclave extraction, distilled water extraction at room temperature). As a result, green tea and rosemary extracts showed relatively high antioxidant activities compared with those of lemon and bamboo leaves. These green tea and rosemary extracts were subsequently added to soymilk and their mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Additionally, enzymatic antioxidants such as superoxide dismutase, catalase, and glutathione peroxidase are also found (Kim et al, 2012). Research is actively underway to develop natural antioxidants derived from plants that can indirectly increase or directly eliminate reactive oxygen species without side effects on the human body (Ryu et al, 2017). The development of safe and highly effective natural antioxidants that can replace the existing antioxidants is an urgent need (Kim et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, enzymatic antioxidants such as superoxide dismutase, catalase, and glutathione peroxidase are also found (Kim et al, 2012). Research is actively underway to develop natural antioxidants derived from plants that can indirectly increase or directly eliminate reactive oxygen species without side effects on the human body (Ryu et al, 2017). The development of safe and highly effective natural antioxidants that can replace the existing antioxidants is an urgent need (Kim et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to recent developments in farming skills, eel's supplies increased, and their consumptions consequently increased (8,9); but there is few research on how to prevent eel's peroxide for improving storage and distribution capabilities. Because green-tea has been reported in many literatures for its high antioxidant effects based on its polyphenol compound having antioxidant capacity (2,3,5,10,11). The aim of this research was to found out the antioxidant effects of green-tea extracts in regards to eel's peroxide when they were pre-applied.…”
mentioning
confidence: 99%